Determination of an age model based on the analysis of the δ 18O cyclicity in a tropical glacier - Calero, Jaqueline L. (2022)
Oxygen isotopes δ18O from a 13 m ice core derived from the Antisana volcano ice cap (0° 28′S, 78° 08′W), Ecuador, were analyzed to generate an age model based on isotopic fluctuations. The inferred age model spans c. 3.6 years, from 1993 to mid-1996, and corresponds to 3.6 cycles of isotopic fluctuations driven by seasonal change in precipitation in western Amazonia. A logarithmic transformation (LT) was performed on the ice core density data to remove the compression effect of accumulated snow affecting the temporal fluctuation of the isotopic signal. A wavelet analysis run on the decompressed isotope signal (LT) showed periodicities of 80, 40, and 20 corresponding to 12, 6, and 3 months, respectively. The results were compared against the isotopic record from the Chimborazo ice core data to validate its temporal match with a hydrological year. The LT isotopic signal showed a significant correlation with the Chimborazo isotopic data (r = 0.69 and p-value<0.001). The methodology applied in this study allowed the reconstruction of 3.6 cycles (3.6 years), showing that age models can be derived from ice cores using oxygen isotope annual fluctuations in tropical glaciers.